Analysis of gender gaps in profession, career and pay - PASNICU, Daniela; MLADEN, Luise (Annals of Spiru Haret University. Economic Series, 2011)
Gender issues and concerns about its incorporation into all Community and national policies enjoy attention, both on the agenda of decision makers from the European Union and the Member States. Moreover, equality between women and men is one of the fundamental principles contained in the Charter of fundamental rights and at the same time, is also one of the founding principles of the EU, because it is based on the principle of “equal pay for equal work” stipulated in the Economics Community Treaty from Rome. The results presented in this article are based on questionnaire-based survey, conducted in ProFeminAntrep project financed on ESF, at national level, which included a sample of 3,200 respondents.